Religious Fundamentalism and Social Distancing: Cause for Concern? - Kumar Ramakrishna (2016)
Home Affairs and Law Minister K. Shanmugam recently warned of “social distancing” as a threat to Singapore’s multi-religious and multi-cultural harmony. Social distancing is in fact evidence of religious fundamentalism, which in tandem with other drivers, could potentially produce extremist violence downstream.